PENGARUH WORD OF MOUTH DAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA IKAN KERING UD. PUTRA PUTRI DI SITUBONDO - Agustin, Putri Dwi; Hamdun, Edy Kusnadi; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2023)
The aim of the study was to determine the effect of Word of Mouth and Product Quality on Repurchase Interest through Consumer Satisfaction as an Intervening Variable in Dried Fish UD. Sons and Daughters in Situbondo. The sampling technique used in this study was simple random sampling of 92 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that word of mouth has a positive and significant effect on consumer satisfaction, product quality has a positive and significant effect on consumer satisfaction, word of mouth has a negative but significant effect on repurchase intention, product quality has a positive effect and significant to repurchase intention, consumer satisfaction has a positive and significant effect on repurchase intention, word of mouth has a positive and significant effect on repurchase intention through consumer satisfaction, product quality has a positive and significant effect on repurchase intention through consumer satisfaction